2021
DOI: 10.3390/jpm11121293
|View full text |Cite
|
Sign up to set email alerts
|

Personal Network Inference Unveils Heterogeneous Immune Response Patterns to Viral Infection in Children with Acute Wheezing

Abstract: Human rhinovirus (RV)-induced exacerbations of asthma and wheeze are a major cause of emergency room presentations and hospital admissions among children. Previous studies have shown that immune response patterns during these exacerbations are heterogeneous and are characterized by the presence or absence of robust interferon responses. Molecular phenotypes of asthma are usually identified by cluster analysis of gene expression levels. This approach however is limited, since genes do not exist in isolation, bu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 52 publications
2
1
0
Order By: Relevance
“… 40 In a separate study using a rhinovirus model of differentiated primary epithelial cells, the induction of type 1 interferon gene expression was evident at 24 hours and peaked at 48 hours in healthy adults, but peaked in adults with asthma at 72 to 96 hours. 41 Similar observations of increased type 1 interferon production have been made in isolated PBMCs from asthmatic children after ex vivo stimulation with rhinovirus 42 and poly(I:C) 43 and in PBMCs 44 and nasal epithelial cells 45 , 46 from children during acute viral wheezing episodes, although heterogeneity in interferon responses was noted. 45 , 46 Together, these findings suggest that type 1 interferon responses during viral exacerbations of asthma are delayed, rather than deficient, and may promote a more inflammatory immune response.…”
Section: Discussionsupporting
confidence: 70%
See 1 more Smart Citation
“… 40 In a separate study using a rhinovirus model of differentiated primary epithelial cells, the induction of type 1 interferon gene expression was evident at 24 hours and peaked at 48 hours in healthy adults, but peaked in adults with asthma at 72 to 96 hours. 41 Similar observations of increased type 1 interferon production have been made in isolated PBMCs from asthmatic children after ex vivo stimulation with rhinovirus 42 and poly(I:C) 43 and in PBMCs 44 and nasal epithelial cells 45 , 46 from children during acute viral wheezing episodes, although heterogeneity in interferon responses was noted. 45 , 46 Together, these findings suggest that type 1 interferon responses during viral exacerbations of asthma are delayed, rather than deficient, and may promote a more inflammatory immune response.…”
Section: Discussionsupporting
confidence: 70%
“… 41 Similar observations of increased type 1 interferon production have been made in isolated PBMCs from asthmatic children after ex vivo stimulation with rhinovirus 42 and poly(I:C) 43 and in PBMCs 44 and nasal epithelial cells 45 , 46 from children during acute viral wheezing episodes, although heterogeneity in interferon responses was noted. 45 , 46 Together, these findings suggest that type 1 interferon responses during viral exacerbations of asthma are delayed, rather than deficient, and may promote a more inflammatory immune response. Our observations of impaired type 1 interferon gene expression in neutrophils at baseline and robust type 1 interferon gene expression after ex vivo poly(I:C) stimulation support this hypothesis and extend knowledge of type 1 interferon responses to neutrophils, which have not been previously studied in asthma.…”
Section: Discussionsupporting
confidence: 70%
“…Recruitment of pDC was delayed and diminished in the airway draining lymph nodes in BN, and there was a complete absence of IRF7 gene networks in the lung. The presence versus absence of IRF7 gene network structures in the rat model prompted us to investigate personal gene network structures in our nasal transcriptomics data from children with severe exacerbations ( 44 ). We observed two major gene network structures in the data centered around IRF7/type I interferons and FCER1G, and we showed that the ratio of interferon- and FCER1G-associated gene network patterns was predictive of recurrence, with low interferon being associated with increased risk of readmission.…”
Section: Interferon Response Patterns As Discrete Endotypesmentioning
confidence: 99%